Analisis Pengaruh Kualitas Produk dan Kualitas Layanan terhadap Loyalitas Nasabah yang dimediasi oleh Kepuasan Nasabah (Studi pada Nasabah Taplus PT Bank Negara Indonesia (Persero) Tbk Kantor Cabang Manado) - Kaunang, Dewi Tresya (Universitas Sam Ratulangi, 2015)
the purpose of this study, to investigate and analyze the positive influence and significance of product quality and service quality to customer satisfaction and loyalty Taplus in PT Bank BNI (Persero) Tbk Manado Branch Office. This research is associative and the selected object is PT BNI (Persero) Tbk Manado Branch Office. Technical analysis of the data used is the assumption Assumption Classic with multicolinearity Test, and Test Normality Heterokesdatisitas with the help of software program SPSS version 22.0 for Windows. The results showed: there is a significant positive effect on the quality of products to customer satisfaction Taplus BNI KCU Manado but there is no significant positive effect on the quality of service to customer satisfaction Taplus BNI KCU Manado. Furthermore, customer satisfaction is significant and gives positive effect on customer loyalty Taplus BNI KCU Manado. Keywords: Product Quality, Service Quality, Customer Satisfaction, Customer Loyalty